The Impact of Digital User Experience on Brand Perception and Consumer Loyalty in the E-Commerce Industry in Indonesia - Susilawati, Agnes Dwita; Wahyudi, Farid; Putra, Wira Pramana; Supriyanto, Wawan; Limpo, Lita (Eastasouth Institute, 2024)
This research investigates the impact of digital user experience (DUE) on brand perception and consumer loyalty within the burgeoning e-commerce industry in Indonesia. Through a quantitative analysis involving 150 e-commerce users, the study examines the relationships between DUE, brand perception (BP), and consumer loyalty (CL) using structural equation modeling (SEM) with Partial Least Squares (PLS) 3.0. The findings highlight the significant positive associations between DUE and both BP and CL, emphasizing the crucial role of user-centric digital platforms in shaping consumer behavior and fostering brand loyalty. Furthermore, the study elucidates the mediating role of BP in the relationship between DUE and CL, underscoring the importance of cultivating favorable brand perceptions to enhance consumer loyalty. These insights offer valuable implications for e-commerce businesses seeking to optimize their digital strategies and cultivate enduring customer relationships in the dynamic Indonesian market landscape.